Validation of the high mortality rate of Malnutrition-Inflammation-Atherosclerosis syndrome: –Community-based observational study–. (1st March 2017) - Sueta, Daisuke; Hokimoto, Seiji; Sakamoto, Kenji; Akasaka, Tomonori; Tabata, Noriaki; Kaikita, Koichi; Honda, Osamu; Naruse, Masahiro; Ogawa, Hisao
Abstract: Background: Malnutrition-Inflammation-Atherosclerosis (MIA) factors significantly and independently affect life prognosis of hemodialysis (HD) patients. We re-evaluated Japanese data, which have progressed ahead from a community-based observational study. The present study was designed to assess the contribution of these MIA factors to the mortality rate of Japanese HD patients in a community of 1.8 million people over a 36-month follow-up period. Methods and results: A total of 5813 patients at 76 facilities were on maintenance HD in the Kumamoto Prefecture. Specifically, 4807 of these patients at 58 institutions were enrolled. Patients who exhibited lower serum albumin and higher serum C-reactive protein levels were defined as "malnourished" and "inflamed", respectively, compared with the median values. Patients who underwent invasive procedures for atherosclerotic diseases were defined as "atherosclerotic". The 36-month all-cause mortality rate in Japanese HD patients was 12.4%. This rate directly correlated with the number of MIA factors. The odds ratio of the all-cause mortality rate markedly and significantly increased as the number of factors increased. The presence of 3 MIA factors in HD patients was a significant predictor of mortality, as evidenced by a multivariate logistic regression analysis. Conclusions: This study clearly demonstrated the close association between MIA syndrome and high mortality in Japanese HD patients. Early detection and the adjustment of MIA factors are mandatory.